Pengaruh Produk, Pelayanan, Promosi, Lokasi Dan BagiHasil Terhadap Keputusan Masyarakat Memilih Bank Syariah(Survey pada BTN Syariah Cabang Surakarta) - Ernawati, Tatik; , Drs.Eko Sugiyanto, SE, M.Si; , Eni Kusumawati, SE, Akt (2015)
This study aimed to get empirical evidence about the influence of the products, services, promotions, location, and for the outcome of the decision of the people choose Islamic banks. This research was conducted at the State Savings Bank (BTN) Syariah Branch of Surakarta with sample of customers who save in BTN Syariah Branch of Surakarta. The number of samples in this study were 100 respondents in BTN Syariah Branch of Surakarta. Sampling was done by using a sampling method convience. Results of the analysis concluded that the results of the classical assumptions do not occur in the problem multicollinearity test, test and test data normality heteroskedastisitas normal distribution. Based on the results of data analysis known that the product, service and profit sharing positive and significant impact on the decisions people choose BTN Syariah Branch of Surakarta. While the promotion and the location does not affect the decision of the people choose BTN Syariah Branch of Surakarta. T test results showed tcount product variable of 2.422 with a significance value of 0.017 (p <0.05) so H1 accepted, service variable indicates tcount of 2.201 with a significance value of 0.030 (p <0.05) so H2 accepted, variable promotional shows tcount amounted to 0.374 with significant value of 0.709 (p> 0.05) so H3 rejected, location variables showed tcount of 0.552 with a significance value of 0.582 (p> 0.05) so that the H4 rejected, and the results show the value of the variable thitung 4.254 with a significance value of 0.000 (p <0.05) so H5 accepted. Keywords: products, services, promotions, location, profit sharing, saving decision.